2014
DOI: 10.1177/2150135114540181
|View full text |Cite
|
Sign up to set email alerts
|

Adult Survivor With Repaired Complete Pentalogy of Cantrell

Abstract: Pentalogy of Cantrell is a very rare condition with very high mortality. We present an adult survivor with a classic pentad who underwent sequential surgical repairs as a neonate, child, and young adult. He required home mechanical ventilation for the first two years of life and subsequently needed noninvasive nocturnal ventilation as an adult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The survival rate was less than 0.8%. 16 However, it has also been reported that older children or adults had satisfactory surgical outcomes and no mortality, 17 18 19 potentially reflecting the condition of their cardiac malformations and differences in the severity of the disease in these patients. In some cases, the intracardiac malformation is not serious; the patient merely has a slight defect of the thorax and abdominal wall and a protruding heart.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate was less than 0.8%. 16 However, it has also been reported that older children or adults had satisfactory surgical outcomes and no mortality, 17 18 19 potentially reflecting the condition of their cardiac malformations and differences in the severity of the disease in these patients. In some cases, the intracardiac malformation is not serious; the patient merely has a slight defect of the thorax and abdominal wall and a protruding heart.…”
Section: Discussionmentioning
confidence: 99%